Design of a 5-ary 1-cube torus network-on-chip - Xing, Cong (2018)
A one-dimensional torus network-on-chip with five switching nodes, which can also be named as 5-ary 1-cube torus, has been designed. The routers in the network can tackle input flow control digits (flits) from three different directions at the same time. In the case of dealing with short messages, round robin protocol is adopted in the input module of the router. Since the data can be transmitted within on cycle, the arbitration scheme is executed on a cycle-by-cycle basis. However, for the transmission of long messages, consecutive cycles are required. Moreover, the transmission process must not be interrupted. Thus, the Grant-Hold circuitry is come up with to guarantee the uninterrupted transmission. When the chosen flit enters and arrives at the output of the switching node, the routing algorithm, which ensures the minimum traversal path, is invoked to determine the output direction taken by the outgoing flit. Consequently, the functionality of bidirectional flits transport has been achieved. In addition, the fabrics of the network are described by Verilog HDL, and the correctness of the network-on-chip as well as the submodules has been verified by corresponding test benches. Keywords: torus network-on-chip, router, Round Robin, Grant-Hold, routing algorithm, bidirectional